2006
DOI: 10.1021/ja064988u
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Nanopatterns Self-Assembled by Adenine−Thymine Quartets at the Liquid/Solid Interface

Abstract: By means of scanning tunneling microscopy (STM), we have observed for the first time well-ordered supramolecular nanopatterns formed by mixing two complementary DNA bases: adenine (A) and thymine (T), respectively, at the liquid/solid interface. By mixing A and T at a specific mixing molar ratio, cyclic structures that were distinctly different from the structures observed by the individual base molecules separately were formed. From an interplay between the STM findings and self-consistent charge density-func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
138
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(145 citation statements)
references
References 58 publications
7
138
0
Order By: Relevance
“…In support of this postulation, molecular recognition between complementary bases, most likely driven by hydrogen bonding alone, has already been observed both at the liquid/solid (HOPG) interface and on the noble Au(111) surface under extreme ultrahigh vacuum (UHV) conditions. [8][9][10] These previous experiments were, however, conducted with nucleobases alone, and hence did not take the presence of deoxyribose into account. It is therefore of utmost importance to explore the role that Watson-Crick hydrogen bonding plays at surfaces in chemical structures that mimic nucleotides so as to address the fundamental question of how the polymerization of nucleotides may have started in the prebiotic soup in the absence of enzymes.…”
mentioning
confidence: 99%
“…In support of this postulation, molecular recognition between complementary bases, most likely driven by hydrogen bonding alone, has already been observed both at the liquid/solid (HOPG) interface and on the noble Au(111) surface under extreme ultrahigh vacuum (UHV) conditions. [8][9][10] These previous experiments were, however, conducted with nucleobases alone, and hence did not take the presence of deoxyribose into account. It is therefore of utmost importance to explore the role that Watson-Crick hydrogen bonding plays at surfaces in chemical structures that mimic nucleotides so as to address the fundamental question of how the polymerization of nucleotides may have started in the prebiotic soup in the absence of enzymes.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] Specific supramolecular architectures can be designed by choosing molecular building blocks with distinct size, geometry, and bonding interaction, as has been demonstrated extensively in solution-based coordination chemistry [7][8][9][10] and, in recent years, on surfaces. [11][12][13][14][15] The technological potential of controlled structural and chemical patterning of surfaces has driven an interest in the rational design of highly ordered and regular networks at solid surfaces, which require selective and directional bonding interactions, such as hydrogen bonding [16][17][18] or metal-organic coordination. [11,13,19,20] Reversible (noncovalent) bonding motifs allow for efficient error-correction during the growth process and long-range structural order in the resulting supramolecular architecture.…”
mentioning
confidence: 99%
“…It was suggested that such structures might offer applications in biocompatible nanopatterned surfaces and for targeted drug delivery. 65 Coadsorption of guanine and cytosine also resulted in ordered assemblies at 1-octanol/graphite interface, where one of the phases consisted of hydrogen-bonded guanine-cytosine dimers (Fig. 7).…”
Section: Co-adsorption Of Different Nucleobasesmentioning
confidence: 99%
“…65 Interestingly, thymine on Au(111) substrate leads to randomly oriented 1D laments, when viewed at low surface coverage, which gets morphed to 2D island-like growth patterns on increasing the coverage area, supported by weak van der Waals forces. The 2D islands could be reverted to 1D laments through STM tip perturbation, suggesting that 2D islands were loosely held compared to more stable laments (Fig.…”
Section: Surface Modification By Thymine (T)mentioning
confidence: 99%